Assessment of the Influence of Asymmetric Triacetate Cellulose Membrane on the Rate of Removal of Middle Molecular Weight Uremic Toxins in Patients Treated with Postdilution Online Hemodiafiltration - Nenadović, Marko; Nikolić, Aleksandra; Stanojević-Pirković, Marijana; Trbojević-Stanković, Jasna; Nikolić, Tomislav; Petrović, Dejan; Djulejić, Vuk (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Postdilution online hemodiafiltration (OL-HDF) effectively removes uremic toxins of middle molecular weight from the blood of patients with end-stage chronic kidney disease. The rate of removal of uremic toxins depends on the type of dialysis membrane, blood flow rate (Qb), net ultrafiltration flow rate (Qnuf), and total convective volume (Vconv). AIM: The aim of this study was to examine the efficacy of asymmetric triacetate cellulose dialysis membrane in patients on post-dilution OL-HDF. METHODS: Thirty-five patients treated with post-dilution OL-HDF hemodiafiltration for at least 3 months were examined. The main parameters for assessing the efficiency of removal of uremic toxins of middle molecular weight are the concentration of β2-microglobulin (β2-M) and interleukin-6 (IL-6) in serum before and after a single session of post-dilution OL-HDF. The followings were used for statistical analysis: Kolmogorov–Smirnov test, Student’s T test for bound samples and Wilcoxon test. RESULTS: The average Vconv was 20.90 ± 3.30 liters/session. The β2-M reduction index during a single session of postdilution OL-HDF was 71.10 ± 6.39%, the IL-6 reduction index was 43.75 ± 15.60%, and the albumin reduction index was 4.55 ± 2.31%. CONCLUSION: The asymmetric triacetate cellulose dialysis membrane effectively removes β2-M and IL-6 during a single session of postdilution OL-HDF. The β2-M reduction index is ∼70%, the IL-6 reduction index is ∼40%, and albumin loss is <4.0 g/4 h. The examined dialysis membrane and dialysis modality prevent the development of amyloidosis associated with dialysis, microinflammation and reduce the risk of developing atherosclerotic cardiovascular diseases in the population of patients treated with regular hemodiafiltration.